Current Status of Transoral Surgery for Patients With Early-Stage Pharyngeal and Laryngeal Cancers in Japan - Sano, Daisuke; Shimizu, Akira; Tateya, Ichiro; Fujiwara, Kazunori; Kishimoto, Yo; Maruo, Takashi; Fujimoto, Yasushi; Mori, Terushige; Kato, Hisayuki; Tsukahara, Kiyoaki; Oridate, Nobuhiko (Frontiers in Oncology, 2021)
As the laryngopharynx is closely related to swallowing, speech, and phonation, it is necessary to consider not only disease control but also a minimally invasive approach for the treatment of laryngopharyngeal cancer. Transoral surgery has been reported to be a minimally invasive method for treating these diseases. Transoral videolaryngoscopic surgery (TOVS) and endoscopic laryngo-pharyngeal surgery (ELPS) have been developed in Japan and recently emerged as treatments for patients with early stage pharyngeal and laryngeal cancers. However, securing an appropriate field of view and a narrow operating space during TOVS or ELPS are critical issues to be resolved for these surgeries. The clinical significance and safety of transoral robotic surgery (TORS) using the da Vinci Surgical System have been widely reported to provide surgeons with increased visualization and magnification, resulting in precise surgical margins and rapid functional recovery. In this context, a multi-institutional clinical study was conducted to evaluate the treatment outcomes of TORS for the treatment of laryngopharyngeal cancer in Japan, and the da Vinci Surgical System for oral robot-assisted surgery for these diseases was approved by the Pharmaceutical Affairs Agency in August 2018. This review provides an overview of the therapeutic effects of TOVS, ELPS, and TORS, with a particular focus on these therapeutic results in Japan.